Body mass index versus waist circumference as predictors of mortality in Canadian adults - Staiano, AE (2012)
BACKGROUND: Elevated body mass index (BMI) and waist circumference (WC) are associated with increased mortality risk, but it is unclear which anthropometric measurement most highly relates to mortality. We examined single and combined associations between BMI, WC, waist–hip ratio (WHR) and all-cause, cardiovascular disease (CVD) and cancer mortality. METHODS: We used Cox proportional hazard regression models to estimate relative risks of all-cause, CVD and cancer mortality in 8061 adults (aged 18–74 years) in the Canadian Heart Health Follow-Up Study (1986–2004). Models controlled for age, sex, exam year, smoking, alcohol use and education. RESULTS: There were 887 deaths over a mean 13 (SD 3.1) years follow-up. Increased risk of death from all-causes, CVD and cancer were associated with elevated BMI, WC and WHR (P < 0.05). Risk of death was consistently higher from elevated WC versus BMI or WHR. Ascending tertiles of each anthropometric measure predicted increased CVD mortality risk. In contrast, all-cause mortality risk was only predicted by ascending WC and WHR tertiles and cancer mortality risk by ascending WC tertiles. Higher risk of all-cause death was associated with WC in overweight and obese adults and with WHR in obese adults. Compared with non-obese adults with a low WC, adults with high WC had higher all-cause mortality risk regardless of BMI status. CONCULSION: BMI and WC predicted higher all-cause and cause-specific mortality, and WC predicted the highest risk for death overall and among overweight and obese adults. Elevated WC has clinical significance in predicting mortality risk beyond BMI.